Bankers’ Perspective on Challenges of Bad Debt Recovery: Empirical Evidence from Commercial Banks of Nepal - Dhakal, Krishna; Khanal, Kiran; Devkota, Niranjan; Paudel, Udaya Raj (Journal of Business and Social Sciences Research, 2023)
The purpose of this paper is to investigate bankers’ perspective on challenges of bad debt recovery in commercial banks of Nepal. This study is based on liquidity management theory and adopts explanatory research design to determine causal relationship between variables. Primary data has been collected from 220 bankers through the structured questionnaire by using KOBO Toolbox. SEM is used to analyze data inferentially. Findings indicate that lending decision and loan risk monitoring are significant to bad debt recovery. Unfavorable methods, availability of accurate and proper information about the loans, lack of payment visibility, and lack of flexible payment options are major challenges of bad debt recovery. Thus, commercial banks of Nepal must develop proper monitoring mechanism and government should develop proper regulation for debt collection.